Quantitative Proteomic Analysis of the Senescence‐Associated Secretory Phenotype by Data‐Independent Acquisition. Issue 2 (1st February 2021) - Neri, Francesco; Basisty, Nathan; Desprez, Pierre‐Yves; Campisi, Judith; Schilling, Birgit
Abstract: Cellular senescence is a complex stress response that induces an essentially permanent cell cycle arrest and a complex secretory phenotype termed the senescence‐associated secretory phenotype (SASP), which drives numerous aging pathologies. Characterization of the SASP can provide insights into aging and disease mechanisms, aging biomarker candidates, and targets for counteracting the deleterious effects of senescent cells. Here we describe a mass spectrometry (MS)‐compatible protocol to (1) generate senescent cells using different stimuli, (2) collect conditioned medium containing proteins secreted by senescent cells (i.e., SASP), and (3) prepare the SASP for quantitative proteomic analysis using data‐independent acquisition (DIA) MS. © 2021 The Authors. Basic Protocol 1 : Generating ionizing radiation‐induced senescent and control cells Alternate Protocol 1 : Generating doxorubicin‐induced senescent and control cells Alternate Protocol 2 : Generating oncogenic RAS‐induced senescent and control cells Alternate Protocol 3 : Generating mitochondrial dysfunction‐induced senescent and control cells Alternate Protocol 4 : Generating atazanavir/ritonavir‐induced senescent and control cells Support Protocol : A multiple‐assay approach to confirm the phenotype of senescent cells Basic Protocol 2 : Generating conditioned medium from senescent cells cultured in low serum and quiescent control cells Alternate Protocol 5 : Generating conditioned medium from senescent cells cultured in complete medium and quiescent control cells Basic Protocol 3 : Quantitative proteomic analysis of the SASP